Development of Web Based Instruction on Circulatory and Lymphatic System - ทองมาก ลีนา (Academic Journal of Thailand National Sports University, 2010)
The purposes of this research were to develop determine quality and efficiency of lesson base instruction on Circulatory and Lymphatic System in Anatomy and Physiology 2 course. The research hypotheses were those the lesson’s quality would be at least in good level, and its efficiency would not be less than the criteria of 80/80. The research was conducted with the 31 second year student of Bachelor curriculum of Education (Physical Education) Program in institute of Physical Education - Chumphon, semester 1, 2007 academic year. How to develop the lesson 1. Select a lesson topic and divided into sub-topics 2. Define the objectives of the lesson to cover the contents of all sub-topics Construct the lesson exercises and tests to measure students learning achievement during and after the learning period. Design and create the lesson contents and exercises as web base instruction with Macromedia Dreamweaver PHP and Perl program. Have the specialists evaluated and suggested the media productions and their evaluation was the used to find out its quality. Find out its efficiency with the population. The results of research were : The development of web base instruction on Circulatory and Lymphatic system in Anatomy and Physiology 2 course was at http://www.ipecp.ac.th/cgi-bin/Circulatory/ The quality of content aspect of web base instruction on Circulatory and Lymphatic system in Anatomy and Physiology 2 course was excellent ( = 4.61, S.D. = 0.28) and the media production was excellent = 4.63, S.D. = 0.19) as well. The efficiency of web base instruction on Circulatory and Lymphatic system in Anatomy and Physiology 2 course was 88.8./89.39.